(untitled) (Bioagro, 2024)
In Mexico, corn cultivation is the basis of the diet; the country plants 6.7 million hectares, with an average yield of 6.6 tons/ha. The objective was to evaluate the most widely used insecticides for the control of Spodoptera frugiperda on the entomofauna associated with corn. A 900 m2 plot was used in the Academic Unit of Agriculture of the Autonomous University of Nayarit during the crop cycle. The insecticides were: chlorpyrifos ethyl, cypermethrin, methomyl and spinetoram and a control, in a randomized block design. Where insecticides were not applied, a parasitism rate of 27,5% was presented, with the main non-target species identified being Pristomerus spinator, Campoletis sonorensis and Cotesia sp. aff. Scitula. In the experimental units treated with insecticide, the rate of parasitism was 0%. Methomyl insecticide (carbamate) was the most aggressive against non-target organisms followed by chlorpyrifos ethyl (organophosphate) while spinetoram (spinosins) was the least aggressive. General active ingredients such as carbamates and organophosphates represent a risk for the diversity of natural enemies.